The Lindahl Equilibrium in Schumpeterian Growth Models: Knowledge Diffusion, Social Value of Innovations and Optimal R&D Incentives - Elie Gray; André Grimaud (Center for Economic Studies and ifo Institute (CESifo), 2014)
What is the social value of innovations in Schumpeterian growth models? This issue is tackled by introducing the concept of Lindahl equilibrium in a standard endogenous growth model with vertical innovations which is extended by explicitly considering knowledge diffusion on a Salop (1979) circle. Completing markets by pricing knowledge allows us to compare the private value of innovations with the social one. This comparison sheds a new light on the consequences of non-rivalry of knowledge and of market incompleteness on innovators' behavior. Then, we notably revisit the issues of Pareto sub-optimality and of R&D incentives in presence of cumulative innovations.
Keywords: D52; O31; O33; O40; O41; 330; Schumpeterian growth theory; Lindahl equilibrium; social value of innovations; Pareto sub-optimality; cumulative innovations; knowledge spillovers